2003
DOI: 10.1002/eqe.294
|View full text |Cite
|
Sign up to set email alerts
|

Seismic risk assessments and GIS technology: applications to infrastructures in the Friuli–Venezia Giulia region (NE Italy)

Abstract: SUMMARYThis paper illustrates the seismic risk preliminary estimates of two di erent groups of structures located on the territory of the Friuli-Venezia Giulia region (NE Italy): the ÿrst group includes some special industrial plants, and the second group includes bridges and tunnels belonging to the regional highway network. The part of the study on special industrial plants tries to evaluate the degree of expected damage, taking into account their structural typology and ground shaking expressed in terms of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 10 publications
(6 reference statements)
0
12
0
2
Order By: Relevance
“…The majority of such systems employ recordings from strong motion networks to characterize seismic events and estimate the damage by use of known inventory of elements exposed to hazard and associated vulnerability relationships. With respect to transportation networks, there have been some attempts to apply seismic risk assessment to motorway systems such as the one in the Friuli-Venezia Giulia region of NE Italy [Codermatz et al, 2003].…”
Section: Introductionmentioning
confidence: 99%
“…The majority of such systems employ recordings from strong motion networks to characterize seismic events and estimate the damage by use of known inventory of elements exposed to hazard and associated vulnerability relationships. With respect to transportation networks, there have been some attempts to apply seismic risk assessment to motorway systems such as the one in the Friuli-Venezia Giulia region of NE Italy [Codermatz et al, 2003].…”
Section: Introductionmentioning
confidence: 99%
“…A similar approach was delineated by Yang et al (1989) and applied to residential buildings of the Friuli Region (Northeastern Italy) using empirical vulnerability estimates derived by the damage observation after the 1976 M 6.1 Friuli earthquake. The approach was successively extended to infrastructures (Codermatz et al, 2003) using the HAZUS methodology (FEMA, 1999). In the present work, the theoretical backgrounds of the direct and probabilistic approaches to the computation of losses are recalled, further developed and explained, and the results of their application are described and commented with regard to the whole country.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, for the Italian territory no data with I EMS ≥ VIII are available joint with ground motion time series. Concerning the macroseismic intensity scale, in some studies (e.g., Codermatz et al 2003) it is concluded that a substantial equality exists between Mercalli-Cancani-Sieberg scale (MCS; Sieberg 1930) and the European definition of macroseismic intensities (MSK-76, EMS-92 and EMS-98). The MCS scale is used mainly to estimate intensities for historical earthquakes.…”
Section: Housner Intensity Versus Ems-98 Intensitymentioning
confidence: 98%